Climate change and geothermal ecosystems: natural laboratories, sentinel systems, and future refugia. (2nd June 2014) - O'Gorman, Eoin J.; Benstead, Jonathan P.; Cross, Wyatt F.; Friberg, Nikolai; Hood, James M.; Johnson, Philip W.; Sigurdsson, Bjarni D.; Woodward, Guy
Abstract Understanding and predicting how global warming affects the structure and functioning of natural ecosystems is a key challenge of the 21st century. Isolated laboratory and field experiments testing global change hypotheses have been criticized for being too small‐scale and overly simplistic, whereas surveys are inferential and often confound temperature with other drivers. Research that utilizes natural thermal gradients offers a more promising approach and geothermal ecosystems in particular, which span a range of temperatures within a single biogeographic area, allow us to take the laboratory into nature rather than vice versa. By isolating temperature from other drivers, its ecological effects can be quantified without any loss of realism, and transient and equilibrial responses can be measured in the same system across scales that are not feasible using other empirical methods. Embedding manipulative experiments within geothermal gradients is an especially powerful approach, informing us to what extent small‐scale experiments can predict the future behaviour of real ecosystems. Geothermal areas also act as sentinel systems by tracking responses of ecological networks to warming and helping to maintain ecosystem functioning in a changing landscape by providing sources of organisms that are preadapted to different climatic conditions. Here, we highlight the emerging use of geothermal systems in climate change research, identify novel research avenues, and assess their roles for catalysing our understanding of ecological and evolutionary responses to global warming.